Adherence to Iron Chelation Therapy and Its Determinants - Sukhmani Sidhu; Shruti Kakkar; Priyanka Dewan; Namita Bansal; Praveen C. Sobti (International Journal of Hematology-Oncology and Stem Cell Research, 2021)
Background: Thalassemia is a chronic disease requiring lifelong treatment. The adherence to regular iron chelation therapy is important to ensure complication-free survival and good quality of life.